Supercomputing : 29th International Conference, ISC 2014, Leipzig, Germany, June 22-26, 2014. Proceedings - Ludwig, Thomas; Meuer, Hans Werner; Kunkel, Julian Martin (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 29th International Supercomputing Conference, ISC 2014, held in Leipzig, Germany, in June 2014. The 34 revised full papers presented together were carefully reviewed and selected from 79 submissions. The papers cover the following topics: scalable applications with 50K+ cores; advances in algorithms; scientific libraries; programming models; architectures; performance models and analysis; automatic performance optimization; parallel I/O and energy efficiency.